Complete Labial Fusion in a Postmenopausal Woman Presenting with Retention of Urine - Dangal, Ganesh; Tiwari, Kenusha Devi; Poudel, Rekha; Bajracharya, Nishma; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin (Journal of Nepal Health Research Council, 2019)
Complete labial fusion with retention of urine is a rare clinical entity. It occurs when the labia are fused in midline, forming a raphe. It usually develops in postmenopausal women with hypoestrogenism. The usual treatment is with topical estrogen and surgical separation followed by some dilatation. Here we present a case of a 58 years’ postmenopausal,unmarried, nullipara woman who came to our emergency ward with retention of urine.She had history of incomplete voiding and dribbling of urine since six months. General examination and investigations were normal. Her clitoris was normal in size, and the labia majora and anus were visualized well; however, the urethral meatus and vagina were not seen because of fused labia minora.Patient required surgical excision of fused labial folds to relieve the retention. Keywords: Labial fusion; postmenopausal; urinary retention.